PENGARUH MODEL DISCOVERY LEARNING TERHADAP HASIL BELAJAR SISWA PADA TEMA DAERAH TEMPAT TINGGALKU - Charianti Saragih; Reflina Sinaga; Saud Maulahe; Darinda Sofia Tanjung (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2020)
This research aimed to analyze the effect of discovery learning model on students’ learning outcomes on the theme of “Daerah Tempat Tinggalku” at grade IV SD Negeri 091363 Huta Tinggir in academic year 2019/2020. The population was all fourth grade students totaling 50 students. Samples were taken by saturated sampling for as many as 50 students who were divided into two groups and each group consisted of 26 and 24 students. The method used in this research was experimental method in order to find out the effect of certain treatments on others conditions. The instrument in this research was "t", in the form of multiple choices. Then, the hypotheses were tested by using t test. Based on the results of statistical calculation, it was revealed that after implementing discovery learning model, the learning outcome of the students in experiment class was included in Good category (the average score = 81.19). Meanwhile, the learning outcome of the students in control class did not improve significantly from the KKM (the average score = 67.1). Moreover, the result of the t-test resulted in the value of t count = 9.790 while t table = 2,055. This means that t count > t table; thus, Ho was rejected and Ha was accepted. This research concluded that there was a significant influence of discovery learning models on the students’ learning outcomes at grade IV SD Negeri 091363 Huta Tinggir in the Academic Year 2019/2020.